Beyond Wage Increases: How Have Unionized Workplaces in Quebec’s Private Sector Adapted to Labour Shortages? - Jalette, Patrice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2025)
How have workplaces in Quebec's unionized private sector adapted to recent labour shortages? Based on original qualitative and quantitative data, we show that these shortages have affected collective bargaining, collective agreements, work organization, working conditions and union life. As a result, workplace actors have had to be pragmatic in adjusting their practices in response to disruptions caused by labour shortages. The originality of our research lies in its broad perspective on the consequences of labour market tension for labour relations, thus highlighting unexplored and unprecedented effects, both positive and negative on employers, workers and unions.